2019
DOI: 10.1097/coc.0000000000000574
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance Therapy in Metastatic Solid Tumors

Abstract: Managing metastatic diseases involves defining the best strategy that is supposed to take into account both efficacy and quality of life. To this end, clinicians use stop and go or maintenance strategies. As a matter of fact, 2 maintenance strategies can be distinguished: continuation maintenance using a drug already present in induction treatment and switch maintenance with a newly introduced drug. Several drugs have been approved as maintenance therapy with several current indications in solid tumors. Questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 88 publications
0
4
0
Order By: Relevance
“…These results also support the benefit of ICI maintenance therapy in patients with advanced-stage or metastatic solid cancers, although only PD-L1 antibody achieved a significant OS difference. In 2019, a study by Rowinski et al [4] reported that although maintenance strategies such as chemotherapy, targeted therapy, and immunotherapy were proven effective, the duration of treatments remained elusive. In this study, the duration of ICI maintenance therapies remained inconsistent, which possibly caused an impact on the outcomes of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results also support the benefit of ICI maintenance therapy in patients with advanced-stage or metastatic solid cancers, although only PD-L1 antibody achieved a significant OS difference. In 2019, a study by Rowinski et al [4] reported that although maintenance strategies such as chemotherapy, targeted therapy, and immunotherapy were proven effective, the duration of treatments remained elusive. In this study, the duration of ICI maintenance therapies remained inconsistent, which possibly caused an impact on the outcomes of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although most patients with advanced-stage or metastatic cancers may respond to previous systemic therapies, the responses are not durable, and maintenance therapy is required to reduce the risk of disease progression and deaths. [4,5] Maintenance treatment options, such as chemotherapy, endocrine therapy, targeted agent, and tumor vaccine, are effective for various malignant tumors, [6][7][8][9] among which systemic chemotherapy is the most commonly used treatment strategy in the clinical setting. However, the overall treatment effect for most tumors is not ideal, and the severe toxicities of chemotherapy usually cause significant hm to patients.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in breast cancer patients, upwards of 80% of patients are living 5 years after diagnosis ( 28 ). Additionally, cytotoxic treatment is becoming a “chronic therapy:” evidence shows duration of chemotherapy and immunotherapy correlates with survival for many cancers ( 29 31 ). As cancer survivors live longer and receive more cumulative cytotoxic therapy, they become more likely to die from ASCVD, emphasizing the importance of ASCVD prevention and treatment in this population.…”
Section: Cytotoxic Therapy and Ascvd Riskmentioning
confidence: 99%
“…Hematopoetic stem cell transplant (SCT) patients are at elevated risk of hypertension and diabetes, and further evidence suggests that SCT is an established accelerator of atherosclerosis (131). A retrospective analysis of 194 patients who underwent allogeneic SCT and survived more than 100 days found that 42.8% of patients developed hypercholesterolemia and 50.8% of patients developed hypertriglyceridemia.…”
Section: Stem Cell Transplantmentioning
confidence: 99%